Adapting Language Models to User Behavior: A Technical Analysis - Ankit Awasthi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The adaptation of transformer architectures to user behavior analysis marks a pivotal advancement in processing event streams and temporal data. While originally designed for natural language processing, these architectures have been successfully modified to handle the unique challenges of user behavior sequences, including concurrent events, variable time intervals, and complex temporal dependencies. Through enhanced positional encoding and specialized attention mechanisms, these models can effectively capture both short-term actions and long-term behavioral patterns in B2C environments. The integration of temporal convolution layers with traditional attention mechanisms enables comprehensive analysis of user interactions, leading to improved predictive analytics, customer journey optimization, and personalized experience delivery across digital platforms.
Keywords: Attention Mechanisms; Event Processing; Sequential Modeling; Temporal Analysis; User Behavior